On The 2,6,6 – Trimethylcyclohex-2-Ene 1,4-Dione Biotransformation Beyond The Exponential Phase Of Baker’s Yeast Type-Ii Growth Curve - Othman, Siti Umiyah (Universiti Sains Malaysia, 2018)
The reduction of ketoisophorone as a substrate has long become an interest for its valuable products as well as its interesting mechanism through biotransformation. A study of biotransformation of ketoisophorone beyond the exponential phase by non-growing cells has been conducted since there is lack of number of research had been done about biotransformation of ketoisophorone during this phase. The main purpose of this research is to study the growth profile of Saccharomyces cerevisiae and to investigate the amount of product which is actinol formed during stationary phase biotransformation. From the first objective, the growth profile was obtained and substrate introduction (ketoisophorone) was deduced to be made at the 12th hour. Biotransformation was carried out in shake-flask by adding non-growing cells of S.cerevisiae into culture medium. A model of 7820 Gas Chromatography was used to analyze the consumption of ketoisophorone, formation of (6R)-levodione as intermediate and (4R,6R)-actinol as the product. The results showed that production of both (6R)-levodione and actinol was only produced in a small amount. It may be due to no or low activity of carbonyl reductase or the conversion of substrate to product was too fast. For the product formation, actinol is strongly depends on the concentration of ketoisophorone. As the concentration of ketoisophorone is lower, the product formation will be lower too. As the time passes, concentration of substrate is reduced as it was consumed by the cells, so the actinol formation was reduced too.